Real-world clinical and service outcomes of pre-bariatric weight loss interventions and post-bariatric outcomes among patients with insulin-treated Type 2 Diabetes living in the UK: public Health and epidemiological approach - Alkharaiji, Mohammed Abdulaziz H. (2020)
In numerous countries globally, the morbid obesity pandemic is increasingly posing a major lifelong disorder. With one-in-four adults classed as obese, while two-thirds are overweight, obesity’s prevalence in England is among the highest in Europe. The effect of obesity and obesity-related comorbidity on the UK’s NHS public health budgets is second only to smoking, estimated to cost £44.7 billion annually. The official UK obesity management is attained via a commissioned service that adopts a four-tiered pathway. The first two tiers are outside of this study’s remit, pertaining to environmental and population-wide schemes for obesity prevention and promotion of a healthy weight and nutritional balanced diet. Tier 3 is a Multidisciplinary Weight Management Service, aimed at those whose obesity is complex and/or is accompanied by medical needs; patients in this tier may be considered for Tier 4, namely bariatric surgery. Exposure to these two clinical tiers is the focused in this thesis, which evaluates the clinical effect and health outcomes of the commissioned clinical interventions.